Direct one-pot conversion of monosaccharides into high-yield 2,5-dimethylfuran over a multifunctional Pd/Zr-based metal-organic framework@sulfonated graphene oxide catalyst - Insyani, Rizki; Verma, Deepak; Kim, Seung Min; Kim, Jaehoon (ROYAL SOC CHEMISTRY, 2017)
A one-pot conversion of monosaccharides (fructose and glucose) into high-yield 2,5-dimethylfuran (2,5-DMF) is demonstrated over a multifunctional catalyst obtained by loading Pd on a Zr-based metal-organic framework (UiO-66) that is deposited on sulfonated graphene oxide (Pd/UiO-66@SGO). The Bronsted acidity associated with UiO-66@SGO activates the fructose dehydration to form 5-hydroxymethylfurfural (5-HMF), while the Pd nanoparticles further convert 5-HMF to 2,5-DMF by hydrogenolysis and hydrogenation. The results show that under the optimized reaction conditions of 160 degrees C and 1 MPa H-2 in tetrahydrofuran for 3 h, the yield of 2,5-DMF is as high as 70.5 mol%. This value is higher than the previously reported values, and the direct conversion of fructose can be achieved without additional purification of 5-HMF from the reaction mixture. In addition, for the first time, glucose is converted to 2,5-DMF with a high yield of 45.3 mol%. A recyclability test suggests that the 4.8 wt% Pd loaded on the UiO-66@SGO catalyst can be re-used up to five times.
Keywords: LIQUID FUEL 2,5-DIMETHYLFURAN; EFFICIENT PRODUCTION; LEVULINIC ACID; BIOMASS; FRUCTOSE; TRANSFORMATION; GLUCOSE; NANOPARTICLES; UIO-66; FURANS